Structural-chemical features and morphology of glauconites in sedimentary iron ore of Bakchar prospect (Western Siberia) - Rudmin M. A. Maksim Andreevich; Reva I.; Gunko A.; Mazurov A. K. Aleksey Karpovich; Abramova R. N. Raisa Nikolaevna (Geophysical Surveying Methods for Ore Deposit Prospecting. Geoinformation Systems in Geophysical Surveys, 2015)
Title screen